PROPOSED TRAINING APPRAOCH TO DEVELOP PHYSICAL ABILITIES AND SKILL OF SHOT STOPPING FREE THROWS FOR HANDBALL GOALKEEPERS - Nada Zeed Mahamad (Universitas Negeri Jakarta, 2025)
Background. Handball is a team sport that receives special attention due to its popularity and the physical, skill, and psychological capabilities of players to implement the plans required by the game, which arouses the enthusiasm of the spectating audience, especially in winning situations. Objectives. The current research aims to develop a training curriculum for handball goalkeepers and to identify the impact of the training curriculum on developing certain physical abilities and blocking free throws. Method. The researcher chose the experimental method with a single experimental group design as it is one of the scientific methods that are appropriate for solving the research problem, and it is one of the most efficient means of reaching reliable knowledge . The research sample was chosen intentionally and their number was 13 handball goalkeepers for the junior category participating in the 2023-2024 sports season. The researcher assumed that they were homogeneous as they were from the same age group. Results. The results of the study showed that the training method led to the development of some physical abilities among the research sample and that the training method led to the development of the free throw blocking skill among goalkeepers. Conclusion. The researcher recommends using the training method under study in training goalkeepers for the junior category in handball and emphasizing the use of physical and motor ability tests periodically to determine the level of these abilities and monitor their development or decline curves.